2019
DOI: 10.21608/ejabf.2019.29299
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and interaction-reality of Acanthamoeba, enteric adenovirus and rotavirus in drinking water, Egypt.

Abstract: Access to safe water is essential to life and public health of human. Nearly, 884 million people about one-sixth of the world's populations are consuming contaminated water. In this study, the occurrence and the molecular characterization of enteric viruses particularly; enteric adenovirus, rotavirus and free-living protozoan Acanthamoeba spp. were determined in 180 tap water samples collected from five Egyptian governorates during December 2016 to November 2017. Moreover, we aimed to verify whether these isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Similar studies have reported the presence of EV, HAV, HEV, HAstV, NoV and RV in chlorinated drinking water in Egypt (Ali et al 2004;El-Senousy et al 2007Rizk and Allayeh 2018). Recently, Gad et al (2019) detected HAdV DNA in 8.9%, and RV RNA in 15.6% of tap water samples from five Egyptian cities including Cairo and Giza. Furthermore, treated tap and kiosk water in Uganda and Ghana have been found to be contaminated with enteric viruses including EV and NoV (GII), respectively (Gibson et al 2011;Sadik 2016).…”
Section: Ground and Surface Watersupporting
confidence: 70%
“…Similar studies have reported the presence of EV, HAV, HEV, HAstV, NoV and RV in chlorinated drinking water in Egypt (Ali et al 2004;El-Senousy et al 2007Rizk and Allayeh 2018). Recently, Gad et al (2019) detected HAdV DNA in 8.9%, and RV RNA in 15.6% of tap water samples from five Egyptian cities including Cairo and Giza. Furthermore, treated tap and kiosk water in Uganda and Ghana have been found to be contaminated with enteric viruses including EV and NoV (GII), respectively (Gibson et al 2011;Sadik 2016).…”
Section: Ground and Surface Watersupporting
confidence: 70%
“…Rotaviruses were detected in drinking water supplies used for infants in about 32.2% of households (Figure 1) which is higher than previously reported for Shandong, China, at 16.7% using a similar technique (Yang et al 2013), southeast France at 7.1% (Gratacap-Cavallier et al 2000), Karachi, Pakistan, at 5% using ELISA (Yousuf et al 2017), and Colombia at 27.3% and 20.5% (Toranzos et al 1986;Pelaez-Carvajal et al 2016). The presence of rotavirus in the 37.8% of drinking water source samples observed in this study was much higher than previously reported results tested using PCR in Benin at 2.1% (Verheyen et al 2009), Peshawar, Pakistan, at 9.47% (Ahmad et al 2016), Karachi, Pakistan, at 23% (Rashid et al 2021), Beijing, China, at 20.3% (He et al 2009), Costa Rica at 8.1% applying somatic coliphage (Barrantes et al 2022), Faisalabad, Pakistan, at 26.6% using Latex agglutination test (Shoaib et al 2019), Southern Africa at 2.0% (Van Zyl et al 2006), and Egypt at 15.6, 8.3, and 23.3% using RT-PCR and multiplex semi-nested RT-PCR (Mahmoud et al 2019;Rizk & Allayeh 2018;Shaheen 2019), while lower than the study in Ghana (Dongdem et al 2010), where 48.1% of water samples tested by multiplex RT-PCR were positive for rotaviruses. This disparity in the prevalence status might be explained by differences between geographic areas with various contributing factors such as socio-economic and cultural factors, access coverage of water, sanitation, and hygiene behavioral practices, and also by the use of different techniques for rotavirus detection having dissimilar sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…G4, G10, and G12 genotypes were also detected in sewage water [89][90][91][92]. During the 2016-2017 season, RV A was detected in tap water in which G1 constituted >50% of all collected cases, followed by the G2, G4, and G9 genotypes [94]. Another study investigated the presence of RV in Nile water [95], and revealed that G1 was the predominant genotype, followed by G2, then G3 and G9.…”
Section: Distribution Of Rotavirus Strains In Environmental Samplesmentioning
confidence: 99%
“…P [6] was also detected in sewage water [89,91,93]. P [8] constituted the predominant genotype of all tap water samples collected [94]. Samples from the Nile River showed that P [8] was the dominant genotype, followed by P [4], then P [6] [95].…”
Section: Distribution Of Rotavirus Strains In Environmental Samplesmentioning
confidence: 99%
See 1 more Smart Citation